A history of 20 years of visionary work in scientific publishing - Vega Villalobos, Nora Agnes (2020)
The Journal Enfermería Actual in Costa Rica started twenty years ago as a teaching project to create an electronic magazine. The initial objective of the journal was to publish the graduation works done by students and research of the teaching staff of the School of Nursing and other professionals in the health field. It was proposed as an innovation of the pedagogical action, based on the generalization of the tele-informatic networks. In this way, information and communication technologies were taken advantage of, in order to favor interactive and dynamic learning of the student body. As well as the dissemination of research results in nursing. But it would also allow it to be used by any professional who required it and anywhere in the world. Before this concern was born, the School of Nursing at the University of Costa Rica did not have any means of dissemination for its production, such as undergraduate theses or graduation papers. On a national level, Nursing only used the Journal of the College of Nurses. In addition, the dissemination of the experiences of the practice of Nursing, was limited to the interest of publication of a few professionals in this area.The genesis of the journal was an inspiration of the main founder, Dr. Ligia Rojas Valenciano, after her graduation from the Doctorate in Education, where she met and involved the Mag. in Curriculum Planning, Ana Guzmán Aguilar, in this adventure.The beginning was marked by very limited human resources, only the two teachers managing the project who assumed the editing and direction. In addition, at the beginning of the process, they took on the secretarial work, along with a graphic designer and, later, scholarship students, who covered various jobs within the editing process.